Predictive Efficacy of the Advanced Lung Cancer Inflammation Index in Hepatocellular Carcinoma After Hepatectomy - Qiu X; Shen S; Lu D; Jiang N; Feng Y; Li J; Yang C; Xiang B (Dove Medical Press, 2024)
Xin Qiu,1,2,* Shuang Shen,1,* Donghong Lu,2 Nizhen Jiang,3 Yifei Feng,3 Jindu Li,1 Chenglei Yang,1 Bangde Xiang1,4,5 1Department of Hepatobiliary Surgery, Guangxi Medical University Cancer Hospital, Nanning, People's Republic of China; 2Department of Gastroenterology, The First Affiliated Hospital of Guangxi Medical University, Nanning, People's Republic of China; 3Guangxi Medical University Cancer Hospital, Nanning, People's Republic of China; 4Key Laboratory of Early Prevention and Treatment for Regional High Frequency Tumor, Ministry of Education, Nanning, People's Republic of China; 5Guangxi Key Laboratory of Early Prevention and Treatment for Regional High Frequency Tumor, Nanning, People's Republic of China*These authors contributed equally to this workCorrespondence: Bangde Xiang; Chenglei Yang, Email xiangbangde@gxmu.edu.cn; chenglei2017yang@163.comBackground: Hepatocellular carcinoma (HCC) presents a significant global health challenge due to its poor prognosis and high recurrence rates post-surgery. This study examines the predictive efficacy of the Advanced Lung Cancer Inflammation Index (ALI) in assessing the post-hepatectomy prognosis of patients with HCC.Methods: A cohort comprising 1654 HCC patients who underwent hepatectomy at Guangxi Medical University Cancer Hospital from 2013 to 2019 was enrolled. Patients were stratified into two groups according to the median ALI level, and then subjected to propensity score matching (PSM) in a 1:1 ratio. Kaplan-Meier survival curves, the traditional Cox proportional hazards (CPH) model, and machine learning (ML) models were employed to analyze and evaluate ALI's prognostic significance. Furthermore, ALI's prognostic value in digestive system tumors was validated via analysis of the National Health and Nutrition Examination Survey (NHANES) database.Results: After applying PSM, a final cohort of 1284 patients, categorized into high and low ALI groups, revealed a significantly reduced survival time in the low ALI cohort. Univariate and multivariate Cox analyses identified ALI, BCLC stage, CK19, Hepatitis B virus (HBV) DNA, lymph node metastasis, and microvascular invasion (MVI) as independent predictors of prognosis. Both traditional CPH and ML models incorporating ALI demonstrated excellent predictive accuracy, validated through calibration curves, time-dependent ROC curves, and decision curve analysis. Furthermore, the prognostic value of ALI in digestive tumors was confirmed in the NHANES database.Conclusion: The ALI exhibits potential as a prognostic predictor in patients with HCC following hepatectomy, providing valuable insights into postoperative survival.Keywords: advanced lung cancer inflammatory index, ALI, hepatocellular carcinoma, HCC, prognosis, Cox regression, machine learning, ML